2013
DOI: 10.1088/0964-1726/22/7/075014
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection by mixed measurements using accelerometers and strain gages

Abstract: This work investigates the relationship between the FRFs (frequency response functions) measured by accelerometers and strain gages utilized widely for investigating structural performance. Modifying the GDM (global-deviation method), this study examines the possibility of damage detection in utilizing both sensors together. The experimental results on the mixed utilization of two sensors show that the SFRF (strain frequency response function) data measured by strain gages in the neighborhood of end supports a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Esfandiari [28] used a decomposed form of Strain FRF to attribute the strain variations to the changes of the structural parameters. Lee and Rahmattalla [29] proposed a method for damage detection using the data collected from both accelerometers and strain gauges. They indicated that dynamic strain data are more sensitive to structural damages as compared with the displacement data.…”
Section: Introductionmentioning
confidence: 99%
“…Esfandiari [28] used a decomposed form of Strain FRF to attribute the strain variations to the changes of the structural parameters. Lee and Rahmattalla [29] proposed a method for damage detection using the data collected from both accelerometers and strain gauges. They indicated that dynamic strain data are more sensitive to structural damages as compared with the displacement data.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to ensure the long‐term stability of structures, damage diagnosis technology that can accurately detect the occurrence of cracks in real time is urgently required. [ 1 ] Two types of diagnostic methods are often employed: contact diagnostics, in which an electrical signal is detected by a n attached strain gauge [ 2 ] or piezoelectric sensor, [ 3 ] and noncontact diagnostics, in which a camera [ 4 ] or LiDAR detector [ 4b,5 ] is employed. Recently, research on self‐reporting materials, which can produce visible signs of deformation or damage via the incorporation of force‐responsive molecules called mechanophores, began to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…As the function of second derivatives of the classical displacement mode shapes (DMSs), strain mode shapes [9] have been applied in structural dynamic modelling, damage detection and dynamic design due to having high sensitivity [10][11][12][13][14]. In recent years, strain measurement based methods have been successfully developed to improve the local outperformance of model updating [15][16][17].…”
Section: Introductionmentioning
confidence: 99%